2007
DOI: 10.1007/s10620-007-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Treatment of Acute Diverticular Hemorrhage Using Endoclips

Abstract: Although colonoscopy is used in the diagnostic evaluation of patients with diverticular hemorrhage, data on colonoscopic treatment outcomes are limited. We reviewed records of inpatients undergoing colonoscopy to identify patients that were colonoscopically diagnosed and treated for acute diverticular hemorrhage. Eleven patients with acute diverticular hemorrhage had active bleeding (n = 7) or non-bleeding visible vessel (n = 4) at colonoscopy. Endoclip treatment (preceded by epinephrine injection in 64%) achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 21 publications
0
85
1
2
Order By: Relevance
“…Hemoclips have been used in different ways (8,9), depending on whether bleeding comes from the neck or the bottom of the diverticulum. All the hemoclips used in our cases were Resolution ® clips (Boston Scientific).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoclips have been used in different ways (8,9), depending on whether bleeding comes from the neck or the bottom of the diverticulum. All the hemoclips used in our cases were Resolution ® clips (Boston Scientific).…”
Section: Discussionmentioning
confidence: 99%
“…Several endoscopic techniques have been described to treat diverticular bleeding, including the injection of epinephrine (5), contact thermal therapy (6), fibrin sealant (7), hemoclips (8,9) or band ligation (10).…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports concerning the colonoscopic management of diverticular bleeding, the clipping method has been found to be effective for hemostasis by nearly closing the diverticular orifice when it is performed either directly on the bleeding point (when visible) or on the vessel area supplying the bleeding point. 15,16 A further advantage is that the metal clips serve as radiographically visible targets for angiographic treatment (super-selection) even if the endoscopic attempts fail or bleeding recurs. These two cases demonstrate that colonoscopic treatment for appendiceal bleeding can be simple, safe, and effective.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] In such cases it has been suggested that the bleeding results from inflammation leading to an exposure of the submucosal vessels. 14 After a colonoscopic diagnosis of appendiceal bleeding, the usual therapeutic procedure is laparoscopic or surgical appendectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a trial by Green et al ( 2 ), a defi nitive bleeding source was identifi ed signifi cantly more oft en in patients with LGIB undergoing urgent colonoscopy vs. elective colonoscopy (42 vs. 22 % , P = 0.03), and no stigmata of hemorrhage were identifi ed in patients undergoing elective colonoscopy following a positive tagged red blood cell scan (mean time to colonoscopy was 38 h). Other series have found that the yield of colonoscopy is higher when performed in the setting of active bleeding vs. electively ( 10,11 ), suggesting that the timing of colonoscopy relative to bleeding is more important than the interval since admission . However, diagnosis alone will have little impact on major clinical outcomes.…”
mentioning
confidence: 95%